Isobaric Vapour-Liquid Equilibrium for Binary System of Trifluoroacetic Acid and Acetone - Li, Yumei; Bai, Peng (Asian Journal of Chemistry, 2011)
Isobaric vapour-liquid equilibrium (VLE) data for trifluoroacetic acid (TFA) and acetone system was measured at 101.33 kPa by using equilibrium still. The results show that TFA and acetone system can form a maximum temperature azeotrope. Thermodynamic consistency of the experimental data was confirmed by means of Herington method. The data was then correlated and calculated by Wilson equation and Vanlaar equation, respectively. Wilson equation is little better than the Vanlaar equation based on the average deviations of temperature and the vapourphase composition. By Wilson equation the boiling temperature of the azeotrope for the experimental system was identified to be 77.62 ºC and the corresponding composition is 0.2459. These agree well with the experimental data.